POLICY OF REGIONAL GOVERNMENT OF MAGELANG REGENCY ON FOREIGN INVESTMENT OF TOURISM - Febri Rizki Kurniawan; Dyah Adriantini Sintha Dewi; Bambang Tjatur Iswanto (Pandecta Research Law Journal, 2019)
Tourism is one of the sources of Original Regional Revenue that is quite promising, when it is managed professionally. With regard to funds, the presence of foreign investment is a very possible solution. From the collected data, in the Regency of Magelang, the presence of foreign investors in tourism is still very little, while such potential is wide open for development. For this reason, this research is entitled "The Policy of the Regional Government of Magelang Regency towards Foreign Investment in Tourism". This study aims to find out how the Regional Government Policy of Magelang Regency in regulating foreign investment in the tourism sector as well as knowing its implementation and also the driving factors and obstacles in the implementation of foreign investment cooperation in tourism.This study is a normative juridical study that uses primary data, secondary data and tertiary data. Data collection is done using library research techniques, observation, interviews and online data search.Based on the results of this study indicate that the Regional Government Policy of Magelang Regency to increase foreign investment, especially in the tourism sector, is still very lacking because there are few foreign investors who invest in Magelang Regency. Based on the driving factors and constraints that exist, the prospect of foreign investment manifested by Magelang Regency Tourism towards the labor sector is very promising because it can open opportunities for employment opportunities for the people of Magelang Regency, and improve the economy in Magelang Regency. However, there are limitations to the Policy of the Regional Government of Magelang District in certain areas regulated by Presidential Regulation Number 58 Year 2014 concerning the Spatial Planning for Borobudur and Surrounding Areas and also the issuance of Regents Regulations governing Foreign InvestmentKeywords: Policy, Foreign Investment, Tourism